2015
DOI: 10.1124/dmd.115.065201
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation and Ubiquitylation Circuitry Controls Pregnane X Receptor Biology in Hepatocytes

Abstract: Several nuclear receptor (NR) superfamily members are known to be the molecular target of either the small ubiquitin-related modifier (SUMO) or ubiquitin-signaling pathways. However, little is currently known regarding how these two post-translational modifications interact to control NR biology. We show that SUMO and ubiquitin circuitry coordinately modifies the pregnane X receptor (PXR, NR1I2) to play a key role in regulating PXR protein stability, transactivation capacity, and transcriptional repression. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 66 publications
1
35
0
Order By: Relevance
“…In this case, SUMOylation acts in a promoter-specific manner. A recent follow-up study demonstrated that PXR is SUMOylated specifically at K108 [85]. It would be interesting to see how SUMOylation of PXR at K108 and adjacent acetylation at K109 influence one another and whether there is functional importance in this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, SUMOylation acts in a promoter-specific manner. A recent follow-up study demonstrated that PXR is SUMOylated specifically at K108 [85]. It would be interesting to see how SUMOylation of PXR at K108 and adjacent acetylation at K109 influence one another and whether there is functional importance in this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…To generate (His) 6 -PXR-SUMO1 and (His) 6 -PXR-SUMO3 linear fusion construct, we used the following PCR primers that introduce XhoI restriction sites and both adds a STOP codon and removes one C-terminal glycine from the SUMO1 and SUMO3: SUMO1- left primer- 5’ GACGGCCTCGAGGCCATGTCTGACCAGGAGGCAAAA 3’; SUMO1- right primer- 5’ GACGGCCTCGAGCTACCCCGTTTGTTCCTGATAAAC 3’; SUMO3- left primer- 5’ GACGGCCTCGAGCCATGTCCGAGGAGAAGCCCAAG 3’; SUMO3- right primer 5’ GACGGCCTCGAGCTATCCCGTCTGCTgCTGGAACAC 3’. The modified SUMO1 and SUMO3 sequences were amplified and then sub-cloned into pShuttle-(His) 6 -PXR-(FLAG) 3 expression vector using the XhoI restriction site that exists in between the last amino acid of PXR and the triple FLAG tag in this expression vector [11]. The FLAG-SUMO3-PXR construct was generated using the following PCR primers to introduce EcoRI restriction sites and removes the STOP codon and one glycine residue from SUMO3: SUMO3- left primer- 5’ GACGGCGAATTCATGTCCGAGGAGAAGCCCAAG 3’; SUMO3- right primer- 5’ GACGGCGAATTCTCCCGTCTGCTGCTGGAACAC 3’.…”
Section: Methodsmentioning
confidence: 99%
“…The FLAG-SUMO3-PXR construct was generated using the following PCR primers to introduce EcoRI restriction sites and removes the STOP codon and one glycine residue from SUMO3: SUMO3- left primer- 5’ GACGGCGAATTCATGTCCGAGGAGAAGCCCAAG 3’; SUMO3- right primer- 5’ GACGGCGAATTCTCCCGTCTGCTGCTGGAACAC 3’. The resulting amplimer was digested with EcoRI and inserted into the EcoRI site that exists between the FLAG epitope and PXR in the previously described pCMV-Tag human PXR expression construct [11]. All expression vectors were sequenced on both strands to ensure the integrity of the resulting open-reading frames.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-translational modifications to the human PXR (hPXR) by phosphorylation and through small ubiquitin-related modifier-and ubiquitin-signaling pathways have been shown to influence the functions of hPXR by modulating intracellular localization and nuclear activation (Lichti-Kaiser et al, 2009;Pondugula et al, 2009;Staudinger et al, 2011;Sugatani et al, 2012Sugatani et al, , 2014Smutny et al, 2013;Elias et al, 2014;Cui et al, 2015). Cyclin-dependent kinase 2 has been shown to phosphorylate hPXR at serine-350 to suppress the binding with retinoid X receptor by maintaining the acetylation of the hPXR protein, thereby downregulating hPXR activity (Lin et al, 2008;Sugatani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%